Antimicrobial susceptibility profile of Aspergillus sp. Strains. impacted soil isolates - Guimarães, Sarah Vieira (2024)
The composition of the landfill soil harbors a diversity of microorganisms that can become pathogenic to humans, such as those of the genus Aspergillus sp. This genus of fungi is characterized by the capacity for genetic alteration to increase resistance. Therefore, the aims of this work were to evaluate the resistance profile of fungi of the genus Aspergillus sp. isolated from impacted landfill soil in the city of Apicum-Açu, state of Maranhão, Brazil. For this purpose, strains of Aspergillus sp. (ASP 2, ASP3 and ASP 4), isolated from impacted soil, using the microculture technique to confirm the gender. The susceptibility of these microorganisms to antifungal agents was evaluated using the Minimum Inhibitory Concentration (MIC) technique by serial microdilution (1:2), in which the antifungals Amphotericin B (16 to 0.0312 mg/L), Voriconazole ( 16 to 0.0312 mg/L) and Itraconazole (8 to 0.0156 mg/L). Isolate ASP2 showed resistance to Voriconazole (>2 mg/L) and indefinite results for the antifungals Itraconazole and Amphotericin B. ASP3 demonstrated sensitivity to Itraconazole (0.5 mg/L) and Voriconazole (0.25 mg/L), however, the result was undefined for Amphotericin B. Finally, the ASP4 isolate showed resistance to Amphotericin B (2 mg/L) and sensitivity to Itraconazole (0.5 mg/L) and Voriconazole (1 mg/L). In this way, the increased resistance of Aspergillus sp. is evident, and the inefficiency of the degree of susceptibility of these drugs against pathologies, thus requiring more in-depth studies and research into new biomolecules, which will allow more efficient results against this genus. of fungi.